Oligomerization of drug transporters: Forms, functions, and mechanisms - Chunxu Ni; Mei Hong (Acta Pharmaceutica Sinica B, 2024)
Drug transporters are essential players in the transmembrane transport of a wide variety of clinical drugs. The broad substrate spectra and versatile distribution pattern of these membrane proteins infer their pharmacological and clinical significance. With our accumulating knowledge on the three-dimensional structure of drug transporters, their oligomerization status has become a topic of intense study due to the possible functional roles carried out by such kind of post-translational modification (PTM). In-depth studies of oligomeric complexes formed among drug transporters as well as their interactions with other regulatory proteins can help us better understand the regulatory mechanisms of these membrane proteins, provide clues for the development of novel drugs, and improve the therapeutic efficacy. In this review, we describe different oligomerization forms as well as their structural basis of major drug transporters in the ATP-binding cassette and solute carrier superfamilies, summarize our current knowledge on the influence of oligomerization for protein expression level and transport function of these membrane proteins, and discuss the regulatory mechanisms of oligomerization. Finally, we highlight the challenges associated with the current oligomerization studies and propose some thoughts on the pharmaceutical application of this important drug transporter PTM.